Hydrogen peroxide vapor decontamination of N95 respirators for reuse. (9th January 2022) - Kenney, Patrick A.; Chan, Benjamin K.; Kortright, Kaitlyn E.; Cintron, Margaret; Russi, Mark; Epright, Jacqueline; Lee, Lorraine; Balcezak, Thomas J.; Havill, Nancy L.; Martinello, Richard A.
Abstract: Objective: The coronavirus disease 2019 (COVID-19) pandemic has led to global shortages of N95 respirators. Reprocessing of used N95 respirators may provide a higher filtration crisis alternative, but whether effective sterilization can be achieved for a virus without impairing respirator function remains unknown. We evaluated the viricidal efficacy of Bioquell vaporized hydrogen peroxide (VHP) on contaminated N95 respirators and tested the particulate particle penetration and inhalation and exhalation resistance of respirators after multiple cycles of VHP. Methods: For this study, 3M 1870 N95 respirators were contaminated with 3 aerosolized bacteriophages: T1, T7, and Pseudomonas phage phi-6 followed by 1 cycle of VHP decontamination using a BQ-50 system. Additionally, new and unused respirators were sent to an independent laboratory for particulate filter penetration testing and inhalation and exhalation resistance after 3 and 5 cycles of VHP. Results: A single VHP cycle resulted in complete eradication of bacteriophage from respirators (limit of detection 10 PFU). Respirators showed acceptable limits for inhalation/exhalation resistance after 3 and 5 cycles of VHP. Respirators demonstrated a filtration efficiency >99 % after 3 cycles, but filtration efficiency fell below 95% after 5 cycles of HPV. Conclusion: Bioquell VHP demonstrated high viricidal activity for N95 respirators inoculated with aerosolized bacteriophages. Bioquell technology can be scaled for simultaneous decontamination of a large number of used but otherwise intact respirators. Reprocessing should be limited to 3 cycles due to concerns both about impact of clinical wear and tear on fit, and to decrement in filtration after 3 cycles.